Integration of routine QA data into mega‐analysis may improve quality and sensitivity of multisite diffusion tensor imaging studies. Issue 2 (27th November 2017) - Kochunov, Peter; Dickie, Erin W.; Viviano, Joseph D.; Turner, Jessica; Kingsley, Peter B.; Jahanshad, Neda; Thompson, Paul M.; Ryan, Meghann C.; Fieremans, Els; Novikov, Dmitry; Veraart, Jelle; Hong, Elliot L.; et al.
Abstract: A novel mega‐analytical approach that reduced methodological variance was evaluated using a multisite diffusion tensor imaging (DTI) fractional anisotropy (FA) data by comparing white matter integrity in people with schizophrenia to controls. Methodological variance was reduced through regression of variance captured from quality assurance (QA) and by using Marchenko–Pastur Principal Component Analysis (MP‐PCA) denoising. N  = 192 (119 patients/73 controls) data sets were collected at three sites equipped with 3T MRI systems: GE MR750, GE HDx, and Siemens Trio. DTI protocol included five b  = 0 and 60 diffusion‐sensitized gradient directions ( b  = 1, 000 s/mm 2 ). In‐house DTI QA protocol data was acquired weekly using a uniform phantom; factor analysis was used to distil into two orthogonal QA factors related to: SNR and FA. They were used as site‐specific covariates to perform mega‐analytic data aggregation. The effect size of patient‐control differences was compared to these reported by the enhancing neuro imaging genetics meta‐analysis (ENIGMA) consortium before and after regressing QA variance. Impact of MP‐PCA filtering was evaluated likewise. QA‐factors explained ∼3–4% variance in the whole‐brain average FA values per site. Regression of QA factors improved the effect size of schizophrenia on whole brain average FA values—from Cohen's d  = .53 to .57—and improved the agreement between the regional pattern of FA differences observed in this study versus ENIGMA from r  = .54 to .70. Application of MP‐PCA‐denoising further improved the agreement to r  = .81. Regression of methodological variances captured by routine QA and advanced denoising that led to a better agreement with a large mega‐analytic study.